PENGEMBANGAN MODEL PEMBELAJARAN MATEMATIKA KNISLEY BERBASIS BRAINSTORMING MATERI STATISTIKA - Lilik Mindarti; Sunismi Sunismi (Jurnal Pendidikan Matematika (JPM), 2015)
The aim of this development is to produce mathemathics Kinsley learning model of Brainstroming-based Statistics of the Tenth grade Senior High School. This study employed research and development design in which the researcher developed a mathematics Kinsley learning model of brainstorming-based statistics for the tenth grade senior high school students. This study operated the model development of Plomp with 4 developmental steps as follows 1) Preliminary Insvestigation, 2) Design, 3) Realisation, 4) Test, evaluation, and Revision. The instruments used were validation  sheet, responses questionnaire, and observation  sheet. 35 students of the class X IPA 4 SMAN 3 Malang were involved in this study. The results of this study were validated by two balidators; expert and practitionaire validators. User responses use to evaluate practicion of product. The validity from validators group and user obtain the score at 3,34, this mean the validity is significant. Then the result of development of mathemathics Knisley learning model of Brainstorming can be implementation on mathematic teaching on the class conventionally.